Empowering Pesantren Institutions through Community-Based Curriculum Reform and Quality Assurance - Musolli Musolli; Rifqotul Husna (Universitas Nurul Jadid, 2026)
The limited capacity of Dewan Masyayikh in developing standardized curricula and internal quality assurance systems remains a critical challenge for many Islamic boarding schools pesantre in Indonesia, particularly in implementing the mandate of Law No. 18 of 2019 on Pesantren. This community engagement program aimed to strengthen the capacity of Dewan Masyayikh to develop a moderation-based curriculum and an Internal Quality Assurance System (IQAS) tailored to the characteristics of pesantren. The program employed a Community-Based Participatory Research (CBPR) approach consisting of four stages: needs assessment, participatory program design, implementation through field visits, focus group discussions, training workshops, and mentoring, followed by evaluation and follow-up. The program involved seven pesantren in the Tapal Kuda region of East Java, Indonesia. The results demonstrated that all participating pesantren successfully produced draft moderation-based curriculum documents and preliminary IQAS documents, established an inter-pesantren collaboration network, and improved participants' capacity to formulate quality standards, evaluation indicators, and internal quality audit mechanisms. Furthermore, each participating pesantren initiated the implementation of an internal quality evaluation cycle as part of its institutional governance. The participatory approach, which actively engaged pesantren leaders, Dewan Masyayikh, and other stakeholders, strengthened institutional commitment and promoted the sustainability of the program. This community engagement model offers a contextual, participatory, and sustainable framework that can be replicated in other pesantren to enhance educational governance, curriculum development, and quality assurance practices while preserving the distinctive values and traditions of Islamic boarding schools.